Mutation breeding of neutral protease-producing strain by N+ implantation - ZHANG Min; ZHAO Cong; LU Fu-ping; CAI Xing-wang; DU Lian-xiang (浙江大学学报. 农业与生命科学版, 2008)
To increase the production of neutral protease, Bacillus subtilis was implanted with low energy N+ beam to breed mutants. The results indicate that the survival rate curve took a “saddle shape” and there was a high positive mutation rate by the dose of (30-50) ×1014 ions·cm-2. Under the implantation conditions of 30 keV and 50×1014 ions·cm-2, strain NP131 was obtained with high yield and stability. The neutral protease yield produced by NP131 was about 15230 U·mL-1, and increased by 71.2% than the original strain. The comparison of the neutral protease activity curve of NP131 and original strain showed that the regularity of the variation was similar. It was indicated that the ion implantation technique is a feasible method in breeding strains.